Towards Strategic and Digital Reform in Uzbekistan’s Real Estate Management: Menuju Reformasi Strategis dan Digital dalam Manajemen Real Estat Uzbekistan - Shukhratovna, Mirdjalilova Dildora (Academia Open, 2025)
General background: Real estate management is a cornerstone for sustainable economic development, particularly in transition economies like Uzbekistan undergoing reform and privatization. Specific background: Despite notable efforts toward digital transformation and structural reform, inefficiencies persist due to underutilized assets, fragmented information systems, and weak strategic planning. Knowledge gap: Existing studies emphasize legal, financial, or valuation models without integrating socio-economic metrics, digital governance, or public-private partnership (PPP) frameworks tailored to transitional economies. Aims: This study aims to develop an integrated methodology for improving the efficiency of real estate object management by combining empirical national data with global best practices. Results: Empirical analysis from 2018–2024 reveals significant improvements in digitalization and investment attraction; however, high vacancy rates and systemic inefficiencies remain. A forecast model predicts investment attraction will exceed 70% by 2030 if reforms persist. Novelty: The research introduces a multi-dimensional approach that incorporates correlational analysis, strategic planning, and PPP mechanisms, aligned with frameworks from the IMF and World Bank. Implications: Findings advocate for a systemic, digital, and socially-oriented management model that enhances fiscal stability, optimizes asset use, and aligns real estate governance with national development priorities. Highlights: Digital transformation is essential for improving real estate management through information systems and strategic planning. High vacancy and poor utilization still persist—about 31% of properties remain unused as of 2024 despite reforms. Investment attraction is rising, projected to reach 70.2% by 2030, driven by digital systems and public-private partnerships. Keywords: Real Estate, Management Efficiency, Digitalization, Investment, Public-Private Partnership